Pre-treatment metastatic biopsy: a step towards precision oncology for urothelial cancer - Klümper, Niklas; Cox, Alexander; Sjödahl, Gottfrid; Roghmann, Florian; Bolenz, Christian; Hartmann, Arndt; Grünwald, Viktor; Faltas, Bishoy M.; Hölzel, Michael; Eckstein, Markus (NAT REV UROL, 2024)
Early metastatic spread and clonal expansion of individual mutations result in a heterogeneous tumour landscape in metastatic urothelial cancer (mUC). Substantial molecular heterogeneity of common drug targets, such as membranous NECTIN4, FGFR3 mutations, PDL1 or immune phenotypes, has been documented between primary and metastatic tumours. However, translational and clinical studies frequently do not account for such heterogeneity and often investigate primary tumour samples that might not be representative in patients with mUC. We propose this as a potential factor for why many biomarkers for mUC have failed to be integrated into clinical practice. Fresh pre-treatment metastatic biopsies enable the capturing of prevailing tumour biology in real time. The characterization of metastatic tumour samples can improve response prediction to immunotherapy, the anti-NECTIN4 antibody–drug conjugate enfortumab vedotin and the FGFR inhibitor erdafitinib. Routine metastatic biopsy can thus improve the precision of identifying driver druggable alterations, thus improving treatment selection for patients with mUC.
CRIS-Team Scopus Importer:2024-11-08